2020
DOI: 10.31234/osf.io/j3m2y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting COVID-19 conspiracist ideation from the Dark Tetrad traits

Abstract: Previous research has suggested that the Dark Triad traits and, specifically, Machiavellianism and psychopathy, are associated with a tendency to believe in conspiracy theories. The current study (N = 203) aimed to replicate and extend the existing research by examining the relationship between the Dark Tetrad traits—Machiavellianism, narcissism, psychopathy, and everyday sadism—and a novel measure of COVID-19 conspiracist ideation. Machiavellian views and psychopathic antisociality were significant positive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Perhaps most critically, the grandiose narcissism latent factorrepresenting the shared variance of the grandiose narcissism measures-and the vulnerable narcissism latent factor-representing the shared variance of the vulnerable narcissism measures-were both associated with the conspiracist ideation latent factor-representing the shared variance of the conspiracist ideation measures. These results add to the modest prior evidence that grandiose narcissism (Cichocka, Marchlewska, & Golec de Zavala, 2016;Kay, 2020Kay, , 2021Malesza, 2020)-and the limited prior evidence that vulnerable narcissism (Jolley & Paterson, 2020;March & Springer, 2019)-are associated with the tendency to believe in conspiracy theories.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Perhaps most critically, the grandiose narcissism latent factorrepresenting the shared variance of the grandiose narcissism measures-and the vulnerable narcissism latent factor-representing the shared variance of the vulnerable narcissism measures-were both associated with the conspiracist ideation latent factor-representing the shared variance of the conspiracist ideation measures. These results add to the modest prior evidence that grandiose narcissism (Cichocka, Marchlewska, & Golec de Zavala, 2016;Kay, 2020Kay, , 2021Malesza, 2020)-and the limited prior evidence that vulnerable narcissism (Jolley & Paterson, 2020;March & Springer, 2019)-are associated with the tendency to believe in conspiracy theories.…”
Section: Discussionsupporting
confidence: 66%
“…Conspiracist ideation was measured using (a) the 15-item Belief in Conspiracy Theories Inventory (BCTI) (Swami et al, 2011) (e.g., "The Apollo moon landings never happened and were staged in a Hollywood film studio"; = .92, ‾ = .43); (b) the 15-item Generic Conspiracist Beliefs Scale (GCB) (Brotherton, French, & Pickering, 2013) (e.g., "The government is involved in the murder of innocent citizens and/or well-known public figures, and keeps this a secret"; = .93, ‾ = .46); (c) the COVID-19 Conspiracist Ideation Scale (CCIS) (Kay, 2020) (e.g., "Prominent scientists are suppressing the truth about COVID-19"; = .80, ‾ = .45); and (d) the 5-item Conspiracy Mentality Questionnaire (CMQ) (Bruder, Haffke, Neave, Nouripanah, & Imhoff, 2013) (e.g., "Many very important things happen in the world, which the public is never informed about"; = .76, ‾ = .39). Participants responded to the BCTI using a nine-point scale (1 = "completely false"; 9 = "completely true").…”
Section: Conspiracist Ideationmentioning
confidence: 99%
“…Personality traits associated with distrust and paranoia 33 , such as the Dark Tetrad traits 30 , and general distrust in authoritieswhether scientists 5,15 , governments 82 including U.S. state governments 22 or other elites 91 and other people 143,144 have been strong predictors of belief in COVID-19 conspiracy theories, which describe COVID-19 to a varying degree as threat 5 (see Table 1). These low levels of trust become a toxic mix in an environment with a constant threat, boosting the adoption of conspiracy beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Personality traits. People scoring high on the Dark Tetrad traits (e.g., Machiavellianism, narcissism, psychopathy, and sadism) 29 seem to be more likely to endorse both COVID-19 30 and non-COVID-19related 31,32 conspiracy theories. This may be the result of a tendency of high-scorers to distrust others and entertain odd beliefs and delusions (e.g., believing that other people are able to read one's mind) 33 .…”
Section: Individual Differencesmentioning
confidence: 99%
“…We also did not include personality variables, such as narcissism or schizotypal personality traits, to predict adherence to protective guidelines or belief in conspiracy theories. It was not the focus of this project, but recent research has indicated roles for personality features as well (Kay, 2020;Larsen et al, 2020). Finally, we measured the role of perceived knowledge, but were not able to measure actual knowledge of COVID-19.…”
Section: Limitationsmentioning
confidence: 98%